DEVELOPMENT OF THE COMPOSITION OF THE MEDICAL AND PREVENTIVE TOOTHPASTE WITH EXTRACT OF SAGE, JUNIPER AND CHAMOMILE - YEFIMOVA, VERONIKA; LUTSENKO, TETYANA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Currently, the trend in the cosmetics industry is to produce natural, ecological products with the preservation of the most complete set of components of the raw materials. The work is devoted to the development of the composition of therapeutic and preventive toothpaste with СО2 extracts of sage, chamomile and juniper. The extracts included in the toothpaste formulation were obtained using supercritical carbon dioxide extraction. In order to choose the optimal conditions for the extraction, we found out the influence of the technological modes of the process on the composition of the extracts. For this purpose, at the first stage, a series of studies on the dependence of the quantitative yield of extracts on pressure was carried out. On the basis of experimental data, the optimal conditions for supercritical fluid extraction were determined. At the second stage of the research, the influence of temperature on the composition of supercritical fluid extracts of sage was studied, which made it possible to determine the temperature parameter of the process. The optimal ratio of extracts in the composition of therapeutic-prophylactic toothpaste has been established.The next stage of research was the selection of the base of the toothpaste, namely an abrasive component that combines a high cleaning capacity with a low abrasion capacity and a thickener (Blanose 7M3 IF). To determine the composition of the toothpaste base, the rheological characteristics of seven formulations of the base, which was obtained from an abrasive component, a thickener, and glycerin, were determined.The toothpaste system is an emulsion-suspension, which during storage can excessively thicken or delaminate, therefore, in order to predict the stability of the rheological properties of the paste, we conducted experiments on the storage of the toothpaste base at a temperature of 25°C for 1.5 months. The work shows that the base of the toothpaste acquires indicators of constant viscosity on the 13-14th day from the moment of release.As a result of the work carried out, a formulation of toothpaste for therapeutic and preventive purposes was developed. In order to confirm the quality of the finished cosmetic product, we examined it according to physic-chemical indicators, namely, appearance, color, smell, taste and hydrogen index (pH).
Keywords: СО2 extract of sage; chamomile and juniper; therapeutic and preventive toothpaste; viscosity; acid number; extraction